2022
DOI: 10.21203/rs.3.rs-1304207/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Combined Endoscopic & Radiologic Intervention For Management Of Acute Perforated Peptic Ulcer : A Randomized Controlled Trial

Abstract: Background : Peptic ulcer perforation is a common and life threatening surgical emergency. The traditional , pedical omental patch is performed for the plugging of perforated peptic ulcer was first described by Cellan-Jones in 1929. Although it is attributed to Graham , who described the use of a free graft of the omentum to repair the perforation in 1937. Many endoscopic methods have been used to treat acute perforated peptic ulcer like over the scope clips , standard endoscopic clips , endoscopic sewing and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…A prospective randomised control trial of 100 patients by Negm et al [ 15 ] comparing endoscopic treatment with surgical treatment concluded that in high-risk surgical patients, combined endoscopic and interventional radiological drainage can effectively treat acute perforated peptic ulcer without the requirement for general anaesthesia, with minimal to no additional morbidity or mortality.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective randomised control trial of 100 patients by Negm et al [ 15 ] comparing endoscopic treatment with surgical treatment concluded that in high-risk surgical patients, combined endoscopic and interventional radiological drainage can effectively treat acute perforated peptic ulcer without the requirement for general anaesthesia, with minimal to no additional morbidity or mortality.…”
Section: Discussionmentioning
confidence: 99%